Phytochemical Screening and Acetylcholinesterase and Butyrylcholinesterase Inhibitory and Thrombolytic Activities of Grewia abutilifolia Vent. & Juss. Leaf - Rafe, Md Rajdoula; Salam, Rayhanus; Hossain, Md Monir; Masud, Mohammad Mehedi (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Cholinesterase inhibitors offer the possible pathway to fight against various types of neurodegenerative diseases. Grewia abutilifolia is used extensively in traditional and folk medicines mainly to improve intellectual capabilities and memory enhancement purposes which support its possible effects against neurodegenerative disorders. We performed preliminary phytochemical screening to observe the presence of potential phytoconstituents of G. abutilifolia leaf extracts and evaluated acetylcholinesterase and butyrylcholinesterase inhibitory properties to measure its anti-cholinesterase activities. Preliminary phytochemical screening confirmed the presence of saponins, tannins, flavonoids, terpenoids, steroids, carbohydrates, coumarins, alkaloids etc. The petroleum ether (PESF), chloroform (CSF) and aqueous soluble fractions (AQSF) of the crude extract of the plant leaf were screened for bioactivities. The highest inhibition of acetylcholinesterase was exhibited by aqueous soluble fraction (AQSF) with IC50 = 5.73 ± 0.59 μg/ml, while the highest inhibition of butyrylcholinesterase was shown by petroleum ether soluble fraction (PESF) with IC50 = 6.57 ± 1.81 μg/ml in a dose-dependent manner. During assay for thrombolytic activity, the chloroform soluble fraction (CSF) revealed highest activity with 25.75 ± 1.62% clot lysis. These results of the present study suggested the effectiveness of G. abutilifolia against various neurological diseases. Dhaka Univ. J. Pharm. Sci. 17(1): 81-86, 2018 (June)